Different underlying mechanisms for face emotion and gender processing during feature-selective attention: Evidence from event-related potential studies. (May 2017) - Wang, Hailing; Ip, Chengteng; Fu, Shimin; Sun, Pei
Abstract: Face recognition theories suggest that our brains process invariant (e.g., gender) and changeable (e.g., emotion) facial dimensions separately. To investigate whether these two dimensions are processed in different time courses, we analyzed the selection negativity (SN, an event-related potential component reflecting attentional modulation) elicited by face gender and emotion during a feature selective attention task. Participants were instructed to attend to a combination of face emotion and gender attributes in Experiment 1 (bi-dimensional task) and to either face emotion or gender in Experiment 2 (uni-dimensional task). The results revealed that face emotion did not elicit a substantial SN, whereas face gender consistently generated a substantial SN in both experiments. These results suggest that face gender is more sensitive to feature-selective attention and that face emotion is encoded relatively automatically on SN, implying the existence of different underlying processing mechanisms for invariant and changeable facial dimensions. Highlights: Dissociation of face gender and emotion processing is illustrated by SN. Attention to face gender generates a pronounced SN. Attention to face emotion does not elicit SN. This dissociation is independent on the dimension of selected features.